Trends in the Recent Information Needs and Uses Literature: A Content Analysis - Julien, Heidi (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This investigation used content analysis to examine the information needs and uses literature published 1990-1994. Analyses measured degree of interdisciplinarity evident in references cited, determined whether this literature was concerned with users' cognitive processes and with systems design and use, and identified research methods used. Secondary analyses included journal type, author type, article type, whether the literature was grounded in theory, and user groups considered. The value of this study was in the development of content analysis categories specifically applicable to the information needs and uses literature, that measure particular aspects of interest to researchers working in this area.